Triplexed CEA-NSE-PSA Immunoassay Using Time-Gated Terbium-to-Quantum Dot FRET - Shashi Bhuckory; K. David Wegner; Xue Qiu; Yu-Tang Wu; Travis L. Jennings; Anne Incamps; Niko Hildebrandt (Molecules, 2020)
Time-gated Förster resonance energy transfer (TG-FRET) between Tb complexes and luminescent semiconductor quantum dots (QDs) provides highly advantageous photophysical properties for multiplexed biosensing. Multiplexed Tb-to-QD FRET immunoassays possess a large potential for in vitro diagnostics, but their performance is often insufficient for their application under clinical conditions. Here, we developed a homogeneous TG-FRET immunoassay for the quantification of carcinoembryonic antigen (CEA), neuron-specific enolase (NSE), and prostate-specific antigen (PSA) from a single serum sample by multiplexed Tb-to-QD FRET. Tb–IgG antibody donor conjugates were combined with compact QD-F(ab’)2 antibody acceptor conjugates with three different QDs emitting at 605, 650, and 705 nm. Upon antibody–antigen–antibody sandwich complex formation, the QD acceptors were sensitized via FRET from Tb, and the FRET ratios of QD and Tb TG luminescence intensities increased specifically with increasing antigen concentrations. Although limits of detection (LoDs: 3.6 ng/mL CEA, 3.5 ng/mL NSE, and 0.3 ng/mL PSA) for the triplexed assay were slightly higher compared to the single-antigen assays, they were still in a clinically relevant concentration range and could be quantified in 50 µL serum samples on a B·R·A·H·M·S KRYPTOR Compact PLUS clinical immunoassay plate reader. The simultaneous quantification of CEA, NSE, and PSA at different concentrations from the same serum sample demonstrated actual multiplexing Tb-to-QD FRET immunoassays and the potential of this technology for translation into clinical diagnostics.